INTRODUCING OLYMPIC EDUCATION AS A MEANS OF INCREASING MOTIVATION AND ENGAGEMENT OF 5-14 YEARS OLD CHILDREN IN PHYSICAL EDUCATION AND SPORT - Hakman, Anna; Galan, Yaroslav; Koshura, Andriy; Beshlei, Olga (My University, 2021)
The purpose of the study is to substantiate the effectiveness of exploiting a set of forms and means of Olympic education that contribute to the formation of motivational prerequisites for children's general overall physical activity. To achieve this goal, the following research methods were used: theoretical analysis of special scientific and methodological literature, documentary materials, abstraction, logical-theoretical analysis, comparative analysis, synthesis, systematization. Results. The paper describes the significance of physical education and sport for the modern young generation. The study proves that one of the important factors motivating children to do sport is to get positive results during such physical activity, which in turn are formed due to the principles of Olympic education. The authors singled out the purpose of Olympic education for children and identified the task of Olympic education to increase motivation for physical education. The article illustrates how Olympic education is introduced into the educational process of schoolchildren providing non-traditional teaching forms that evoke positive emotions in children and stimulate them to study. Conclusions. Summarizing the above, to encourage children more effectively to do physical activities it is necessary to do the following: to exploit various non-standard forms and methods of teaching; apply various exercises and tasks that are not included in the curriculum; create conditions for sufficient, comprehensive physical activity of schoolchildren; promote extracurricular educational work with learners and their parents to promote a healthy lifestyle. Accordingly, Olympic education is an effective means of increasing young people's motivation to do sport and engage in physical education.
Keywords: : Olympic education, motivation, New Ukrainian School.